Attentional impairments following right hemisphere damage with and without hemispatial neglect: A comparative study. Issue 3 (4th May 2018) - Wong, Cristina Elizabeth Izábal; Branco, Laura Damiani; Cotrena, Charles; Joanette, Yves; Fonseca, Rochele Paz
ABSTRACT: This study aimed to evaluate the performance of patients with right hemisphere damage (RHD) with or without hemispatial neglect (HN) on a cancellation task. The study involved 31 control participants and 31 patients with RHD, matched by age, education, and frequency of reading and writing habits. The numbers of omission and random errors as well as the mean time to task completion were compared between adults with and without RHD, as well as between patients with and without HN. The latter made more left-sided omission errors, and more overall omission errors, than patients with RHD and no HN. The location of the first target canceled differed between subjects with RHD and control participants, as well as between patients with and without hemineglect. The use of organized vs. disorganized search strategies did not differ between groups. Further studies are required to investigate the performance of patients with HN of different levels of severity.